Komparasi Nilai Sufistik dalam Terapi Spiritual Emotional Freedom Technique dengan Terapi Mind Healing Technique - Rahmi, Rahmi; Nurjanah, Dian Siti; Naan, Naan (Jurnal Riset Agama, 2023)
Spiritual Emotional Freedom Technique (SEFT) therapy and Mind Healing Technique (MHT) therapy have similar Sufistic values which make perceptions equalize the meaning of the Sufistic values of the two therapies. This research aims to find the sufistic values contained in SEFT Therapy, explain the sufistic values contained in MHT Therapy, and most importantly to compare the sufistic values contained in SEFT therapy and MHT therapy. This research uses a qualitative approach with the research method Library Research or Library Study and Internet Searching or Internet Study. The results obtained from this research are that SEFT Therapy and MHT Therapy have three similar Sufistic values which have different meanings. The comparison of Sufistic values obtained from the two therapies is surrender, sincerity and gratitude. Surrender in SEFT Therapy is seen as an attitude of graceful acceptance of whatever happens in life, while surrender in the MHT view is a healing effort that does not force the results because it believes that healing is the right of Allah SWT. According to SEFT, sincerity refers more to blessing, which is a condition where a person will not complain about any misfortune that occurs in his life, then according to MHT, sincerity is sincerity that knows no boundaries and is selfless for anything given to other people. Lastly, the meaning of gratitude in SEFT is recognition of all the blessings that have been given by Allah SWT. while MHT interprets gratitude as an effort to enjoy the blessings given by Allah SWT.